The involvement of Muslims in the festivals of non-Muslim community in Malaysia from the Islamic perspective - Basri, Ibrahim; Wan Mohd Yusof, Wan Chik; Yendo, Afgani @ Eusoff (Medwell Journals, 2016)
This study aims to analyze the involvement of Muslims in the festivals of the non-Muslim community in Malaysia from the perspective of Islam. The reason being is this issue has given rise to different perceptions within the Muslim community in Malaysia, between those who allow it because they assume it was no more than celebrating the customs and culture of non-Muslim community and those who forbid it because they believe it resembles the religious practice and creed of the non-Muslims. This study is based on a literature review by collecting data from the books of siyasah (policy), fiqh (Islamic jurisprudence), tafsir (exegesis) and Hadith lectures which were analyzed and then a conclusion was drawn. This study found that Muslims are strictly forbidden to participate in a festival that involves the faith practice of the non-Muslims but are allowed to participate if it involves the aspects of culture and tradition as practiced by the non-Muslims in their festivals in Malaysia such as attending an open house and congratulating them either by words or by card. However, the Muslims are required to abide to some specified regulations. In both of the above issues, there is no resemblance with the non-Muslim citizens in terms of faith which is forbidden by Islam rather it was more in the form of celebrating the customs and traditions of the community only which does not contradict the teachings Islam.